Endosomal vacuoles of the prepupal salivary glands of Drosophila play an essential role in the metabolic reallocation of iron - Farkaš, Robert; Beňová-Liszeková, Denisa; Mentelová, Lucia; Beňo, Milan; Babišová, Klaudia; Trusinová-Pečeňová, Ludmila; Raška, Otakar; Chase, Bruce A; Raška, Ivan (Development, growth & differentiation, 2018)
In the recent past, we demonstrated that a great deal is going on in the salivary glands of Drosophila in the interval after they release their glycoprotein-rich secretory glue during pupariation. The early-to-mid prepupal salivary glands undergo extensive endocytosis with widespread vacuolation of the cytoplasm followed by massive apocrine secretion. Here, we describe additional novel properties of these endosomes. The use of vital pH-sensitive probes provided confirmatory evidence that these endosomes have acidic contents and that there are two types of endocytosis seen in the prepupal glands. The salivary glands simultaneously generate mildly acidic, small, basally-derived endosomes and strongly acidic, large and apical endosomes. Staining of the large vacuoles with vital acidic probes is possible only after there is ambipolar fusion of both basal and apical endosomes, since only basally-derived endosomes can bring fluorescent probes into the vesicular system. We obtained multiple lines of evidence that the small basally-derived endosomes are chiefly involved in the uptake of dietary Fe3+ iron. The fusion of basal endosomes with the larger and strongly acidic apical endosomes appears to facilitate optimal conditions for ferrireductase activity inside the vacuoles to release metabolic Fe2+ iron. While iron was not detectable directly due to limited staining sensitivity, we found increasing fluorescence of the glutathione-sensitive probe CellTracker Blue CMAC in large vacuoles, which appeared to depend on the amount of iron released by ferrireductase. Moreover, heterologous fluorescently-labeled mammalian iron-bound transferrin is actively taken up, providing direct evidence for active iron uptake by basal endocytosis. In addition, we serendipitously found that small (basal) endosomes were uniquely recognized by PNA lectin, whereas large (apical) vacuoles bound DBA lectin.
Keywords: endozomy; vakuoly; prepupal period; Iron Compounds; Fluorescent Dyes; metamorphosis; fluorescenční barviva; Salivary Glands; Animals; basal and apical endosomes; iron reallocation; zvířata; transferrin uptake; salivary glands; Pupa; Endosomes; Drosophila melanogaster; kukla; Vacuoles; sloučeniny železa; slinné žlázy